Hubungan Adiksi Smartphone dengan Kualitas Tidur pada Anak Pra Sekolah di PAUD Anggrek Kelurahan Tamansari Kabupaten Bondowoso Tahun 2025 - Dian Ayu Oktaviane; Iis Hanifah; Suhartin (MUTIARA: Jurnal Ilmiah Multidisiplin Indonesia, 2026)
The decline in sleep quality among preschool children has become a significant concern due to its impact on physical health and cognitive development, one of which is influenced by excessive smartphone use. This study addresses the research problem of whether there is a relationship between smartphone addiction and sleep quality in preschool children. The aim of this study is to analyze this relationship among children at PAUD Anggrek, Tamansari Village, Bondowoso Regency, in 2025. The research employed a quantitative approach with a cross-sectional design, involving the entire population of 30 parents as the sample using a total sampling technique. Data were collected through structured questionnaires and analyzed using the chi-square test at a 5% significance level. The results revealed a significance value of 0.000 < 0.05 and a calculated chi-square value of 22.502, which is greater than the chi-square table value of 3.481, indicating a significant relationship between smartphone addiction and sleep quality in preschool children. The findings conclude that higher levels of smartphone addiction are associated with poorer sleep quality in children. The novelty of this study lies in its focus on preschool children within early childhood education settings using a behavioral approach to technology use, which remains relatively underexplored in the local context. These findings provide important implications for parents and educators to regulate smartphone use in order to support optimal sleep quality in children.